SOCIO-PSYCHOLOGICAL SIGNIFICANCE OF THE LEVEL OF SELF-ESTEEM IN THE FORMATION OF A CHILD'S PERSONALITY AT AN EARLY SCHOOL AGE - T. Suleymanova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article reveals the socio-psychological significance of the self-assessment process in the formation of a child's personal qualities during this period of ontogenesis.